Do loyalty cards enhance loyalty in the pharmaceutical sector? - Marques, S. H.; Cardoso, M. G. M. S.; Lindeza, A. C. A. (Journal of Relationship Marketing, 2017)
This paper aims to analyze the influence of the “Portuguese Pharmacies card” (PP card) on the pharmacies’ customers behaviour. It also intends to examine whether marketing stimuli influence consumers’ buying behavior with regard to non-prescription medicines / health and wellness product / pharmaceutical services (NP/HW/PS) and to understand if the consumer social-demographic characteristics influence purchase decisions and customers’ loyalty. The investigation is based on the results obtained through an online survey. Exploratory descriptive analysis, based on a sample of 385 customers, is used to empirically verify the hypothesis under study. The Marketing of stimuli considered in this research include four communication tools: advertising, sales promotions, word of mouth and the sales force. According to the results obtained, the degree of influence attributed to these various communication tools in the buying decision does not differ significantly in terms of socio-demographic categories. On the other hand, the purchase volume of NP/HW/PS is significantly dependent on the influence of advertising and sales promotions in the purchase decision. Furthermore, impulse buying of NP/HW/PS is significantly dependent on the influence of advertising, promotions and WOM. We conclude that the Portuguese Pharmacies card indeed contributes to customer loyalty in the establishments where it is present. In order to meet customer expectations, a loyalty program should be adjusted over time, seeking to stimulate the satisfaction and reliance in this program.